The Lack of Consensus Among Catholics for Establishing New Elementary Schools - Cieslak, Michael J. (Catholic Education: A Journal of Inquiry and Practice, 2006)
For a century Catholic schools have formed the basis for a strong system of acculturation into Catholic identity and values. Catholic schools provided a low-cost basic education and served as a common school for all social classes of Catholics. This system has weakened considerably in the last decades. Between 1970 and 2000 there was a net loss of 3,595 Catholic schools in the United States, a 29.9% decline. In addition, the nature of these schools seems to be changing as the percentage of total Catholic school enrollment made up by non-Catholics has increased ten-fold in 30 years. Many Catholic Schools seem to have pursued increased academic excellence at the expense of religious acculturation. This paper examines diocesan data to determine the extent to which Catholics still consider Catholic elementary schools to be important. Findings include survey data on school importance from 55,000 diocesan Catholics. I addition, parishioner survey results are presented from two suburban parishes, each of which is considering establishing a parochial elementary school. If new elementary schools are going to be established, a way must be found for Catholics to arrive at a consensus on this issue.